Black quanta. On the thermodynamics of the black holes - Apostol, M (Annals of Mathematics and Physics, 2019)
It is shown that the quantized internal motion of the black holes consists of Planck quanta (Planck mass, length, time, etc), which may be called black quanta. The mass of the black hole is a integral multiple of the Planck mass, and the radius of the black hole (Schwarzschild radius) is an integral multiple of the Planck length. This circumstance arises from the proportionality of the black hole radius and mass. The statistical physics and the thermodynamics of the black holes are derived herein from the statistical motion of the black quanta.